The Spirit of '45 - Loach, Ken (Dogwoof, 2013)
1945 was the year when the war against fascism had been won and for many it was time to begin a new struggle for a better, more equal society. Young people coming back from the war, women, many for the first time, joined their trades unions and joined those with memories of the First World War, determined never to return to the "them and us" times when a small, rich elite ruled over the masses living and working in poverty. This film is a timely reminder of how that utopia was built by ordinary men and women working together and, sadly, how much of it has now been destroyed. Using a mix of archive film and contemporary interviews, Loach shows us how this all came about and why it was so necessary. [www.eyeforfilm.co.uk]